Practical method in the diagnosis of diabetic ketoacidosis: end-tidal carbon dioxide - Kayalı, Ahmet; Bora, Ejder Saylav (The European Research Journal, 2024)
Objectives: Diabetic ketoacidosis (DKA) poses a life-threatening risk in uncontrolled diabetes. Current diagnostic criteria rely on invasive measures, leading to potential delays in treatment initiation. This study aimed to assess the diagnostic utility of noninvasive end-tidal carbon dioxide (EtCO2) measurements in DKA patients. Methods: A prospective, cross-sectional study was conducted in a tertiary-level Emergency Medicine Clinic from January 2021 to January 2023. Participants included adults with DKA symptoms and those with stable vital signs as controls. EtCO2 levels were measured using a capnograph device. Diagnostic criteria for DKA were blood glucose ≥250 mg/dL, ketonuria, ketonemia, and metabolic acidosis (pH<7.3 or bicarbonate <15 mEq/dL). Statistical analysis was performed using SPSS Statistics. Results: Of 730 participants, 120 had DKA, 410 did not, and 200 served as controls. EtCO2 levels significantly differed between DKA, non-DKA, and control groups (P<0.05). EtCO2 correlated with pH, lactate, base deficit, and bicarbonate (P<0.05). ROC analysis showed an AUC of 0.86 for EtCO2 in diagnosing DKA (P<0.01), with 91.67% sensitivity and 74.39% specificity at a cut-off value 23.7. Conclusion: This study suggests that EtCO2 measurement is a valuable noninvasive tool for diagnosing and assessing the severity of DKA in the emergency department. An EtCO2 threshold of <23.7 could prompt consideration of DKA in patients with elevated blood glucose levels. More extensive multicenter studies are warranted to validate these findings further. EtCO2 measurement could facilitate early DKA diagnosis and improve patient outcomes.